2022
DOI: 10.1111/imj.15884
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of critically ill patients with one, two and three doses of vaccination against COVID‐19 in Australia

Abstract: Background Vaccination has been shown to be highly effective in preventing death and severe disease from severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection. Currently few studies have directly compared vaccinated and unvaccinated patients with severe COVID‐19 in the intensive care unit (ICU). Aims Our aim was to compare the clinical characteristics and outcomes of vaccine recipients and unvaccinated patients with SARS‐CoV‐2 infection admitted to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 38 publications
2
12
0
5
Order By: Relevance
“…High flow nasal oxygen and non-invasive mechanical ventilation were implemented in 79 (79%) and 18 (18%) patients, respectively. Mechanical ventilation was initiated in 48 (48%) with a median duration of 11 [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] days. Acute kidney injury was diagnosed in 25 (25%) patients and 11 (11%) required renal replacement therapy.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…High flow nasal oxygen and non-invasive mechanical ventilation were implemented in 79 (79%) and 18 (18%) patients, respectively. Mechanical ventilation was initiated in 48 (48%) with a median duration of 11 [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] days. Acute kidney injury was diagnosed in 25 (25%) patients and 11 (11%) required renal replacement therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Outcomes. During a median ICU length-of-stay of 8 [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] days, 34 (34%) patients exhibited a respiratory superinfection, and 31 (31%) patients died (Table 2). Main causes of death were refractory ARDS in 16 (52%) patients, multi-organ failure in 11 (35%) patients, limitation of life support because of an expected poor outcome in 3 (10%) patients, and septic shock secondary to ventilator-acquired pneumonia in one (3%) patient.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Well-designed human studies to address the question of a combined impact of coronavirus infection and subsequent Covid-19 vaccination are lacking. However, a recent study by Otto and colleagues concluded that Covid-19 infection can cause severe disease and death in vaccine recipients, particularly in older adults and those with comorbidities [5]. Given the fact that SARS-CoV-2 viral variants are highly transmissible and have already infected the majority of the populations in westernized countries, such concerns regarding the combined impact of natural infection and subsequent vaccinations could have serious public health implications, particularly in light of ongoing Covid-19 booster campaigns worldwide.…”
Section: Of 15mentioning
confidence: 99%